(untitled) (Global Journals of Research in Engineering, 2012)
Samples of domestic sewage obtained from a sewage treatment plant located in Warri, Nigeria were analysed for two pollution characteristics such as suspended solids (SS) and permanganate value (PV). Values obtained from the analysis were used to assess the possible relationship between the two pollution characteristics using correlation and regression analysis. Mean values of the suspended solids (SS) ranged between 200.0mg/l and 380.0mg/l while mean values of the permanganate values ranged between 162.2mg/l and 286.0mg/l. The correlation coefficient, r was 0.9577. The analysis indicates that real, strong and significant linear relationship exists between suspended solids and permanganate value in the domestic sewage